Writing generator: a study on the use of Transitional Markers in Academic Writing / Alice Shanthi... [et al.] - Alice, Shanthi; Xavier, Thayalan; Lim, Teck Heng; Jane, Xavierine (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Coherence and cohesion are often considered an abstract and difficult area in the teaching of writing. The present study attempts to identify the categories of transitional markers (TM) used by students who have been taught using the Cycle 1 Writing Generator Beta 1.0 developed by the researchers in a writing class, and whether students are able to retain the skills of using TMs effectively in later writing. The Writing Generator is a Microsoft word tool that prompt student to choose from a list the formulaic phrases and expressions when they write expository essays. Using descriptive statistics, it was revealed that transitional markers were used by these students in their pre-test, post-test and also delayed post-test. The findings show a significant difference in the frequency of TMs used in the pre- test and post-test (p=.000). Though students failed to retain aspects of TMs in delayed post-test without the use of Writing Generator, the t-test found no significant difference between the post-test and delayed post-test (p=.302). The result indicates that the Writing Generator is able to condition students to choose TMs that bring about unity in their writing even they do not use the tool. The study indicates that the Cycle 1 Writing Generator Beta 1.0 could be developed further with extra features for Cycle 2 Beta 2.0 that could facilitate students’ uptake of academic writing skills more effectively among students.